2019
DOI: 10.3892/ijo.2019.4844
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cycling as a novel thermal therapy to synergistically enhance the anticancer effect of propolis on PANC‑1 cells

Abstract: Hyperthermia (HT) has shown potential in cancer therapy. In particular, it appears to sensitize cancer cells to chemotherapy. However, a major concern associated with HT is that the thermal dosage applied to the tumor cells may also harm the normal tissue cells. Besides, the drugs used in HT are conventional chemotherapy drugs, which may cause serious side effects. The present study demonstrated a novel methodology in HT therapy called thermal cycle (TC)-HT. With this strategy, a therapeutic window with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…One group showed that both extrinsic (hot air and water bath), or iron oxide nanoparticle based magnetic hyperthermia can damage collagen architecture in hetero-spheroids of Panc1 cells and WI-38 fibroblasts leading to cell death, but without specifying the contribution of Panc1 to this [ 51 ]. Another study demonstrated mitochondrial-driven apoptosis of Panc1 tumor cells after using PCR thermal cycling-based heating to 44 °C, which, however, was well above the conventional 42 °C therapeutic temperature [ 52 ]. In our present study, mEHT monotherapy at 42 °C and mEHT in combination with radiotherapy provoked a significantly elevated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One group showed that both extrinsic (hot air and water bath), or iron oxide nanoparticle based magnetic hyperthermia can damage collagen architecture in hetero-spheroids of Panc1 cells and WI-38 fibroblasts leading to cell death, but without specifying the contribution of Panc1 to this [ 51 ]. Another study demonstrated mitochondrial-driven apoptosis of Panc1 tumor cells after using PCR thermal cycling-based heating to 44 °C, which, however, was well above the conventional 42 °C therapeutic temperature [ 52 ]. In our present study, mEHT monotherapy at 42 °C and mEHT in combination with radiotherapy provoked a significantly elevated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The heat generated by microwave also induced protein aggregation [ 30 ]. Hyperthermia used for anticancer therapy operates on similar principles [ 32 ]. The findings demonstrate how SAM can measure and evaluate heat-induced cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GnRs-loaded films showed a significant increase in temperature. To achieve local hyperthermia, and therefore a biological response of cell death or regeneration, heating cycles may be needed in order to maintain a temperature over 43 • C for a period of time [42,43]. Therefore, irradiation of polymeric films was conducted for 3 cycles of 10 s each, followed by cooling until room temperature, and thermal images were taken before and after this to calculate the increase in temperature.…”
Section: Thermal Studies Of Gnr-loaded Polymeric Filmsmentioning
confidence: 99%